(untitled) (Research, Society and Development, 2024)
This research aimed to identify and analyze the most effective clinical practices in the management of childhood polytrauma. To carry out the data collection, the main scientific and academic databases that offer access to peer-reviewed articles and relevant studies were selected. The databases included were PubMed, Scopus, Web of Science and LILACS. These databases were chosen due to their scope and the quality of the publications they index, ensuring the inclusion of relevant and up-to-date studies on the topic. The review of clinical practices in the management of childhood polytrauma showed that the systematic application of screening protocols, the advanced use of imaging technologies and early intervention are fundamental to improving clinical outcomes. The analysis revealed that Advanced Trauma Life Support (ATLS) and chest drainage practices, among other approaches, have demonstrated significant effectiveness in reducing mortality and improving the functional recovery of child victims of trauma. Furthermore, collaboration between multidisciplinary teams and the implementation of individualized rehabilitation programs contribute significantly to the quality of care and ongoing support during recovery. However, the research identified several limitations, including variation in guidelines and protocols between different institutions and regions, and the persistence of outdated practices in some centers. These inconsistencies can lead to discrepancies in clinical results and highlight the need for greater uniformity and continuous updating in clinical practices.